Development of the IDCIR Mathematics Learning Model to Improve Junior High School Students' Problem-Solving and Creative Thinking Skills - Sufri, Sufri Mashuri; Tahmir, Suradi; Ahmad Talib; Ihsan, Hisyam (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2025)
This study aims to develop and validate the IDCIR (Incubation, Divergence, Convergence, Innovation, Reflection) mathematics learning model as an effort to improve problem-solving skills and creative thinking abilities of junior high school students. The background of this research is grounded in the low levels of numeracy and mathematical reasoning abilities among Indonesian students, as reflected in the results of PISA 2022 and AKM 2024. To address these issues, this study employs a Research and Development (R&D) approach by adapting the Plomp model, which includes the stages of preliminary investigation, design and development, as well as implementation and assessment. The resulting product consists of a learning model along with supporting materials such as lesson plans, teacher's guidebooks, student textbooks, student worksheets, and assessment instruments. Validation was conducted by experts in subject matter, pedagogy, and evaluation, showing that the IDCIR model meets the validity criteria in terms of content, construct, language, and visual design of the learning materials. Practicality testing in three schools indicated that the model can be implemented effectively, its syntax is easy for teachers to follow, and students responded positively to the learning activities. Furthermore, effectiveness testing using a pretest–posttest control group design revealed that students who learned through the IDCIR model experienced significant improvements in problem-solving skills, creativity indicators (fluency, flexibility, originality), and learning engagement compared to students in the control group. Thus, the IDCIR model is declared valid, practical, and effective, and can be recommended as an innovative alternative in mathematics instruction to support the achievement of 21st-century competencies.